A RID-like putative cytosine methyltransferase homologue controls sexual development in the fungus Podospora anserina - Grognet, Pierre (PLoS Genet, 2019)
DNA methyltransferases are ubiquitous enzymes conserved in bacteria, plants and opisthokonta. These enzymes, which methylate cytosines, are involved in numerous biological processes, notably development. In mammals and higher plants, methylation patterns established and maintained by the cytosine DNA methyltransferases (DMTs) are essential to zygotic development. In fungi, some members of an extensively conserved fungal-specific DNA methyltransferase class are both mediators of the Repeat Induced Point mutation (RIP) genome defense system and key players of sexual reproduction. Yet, no DNA methyltransferase activity of these purified RID (RIP deficient) proteins could be detected in vitro. These observations led us to explore how RID-like DNA methyltransferase encoding genes would play a role during sexual development of fungi showing very little genomic DNA methylation, if any. To do so, we used the model ascomycete fungus Podospora anserina. We identified the PaRid gene, encoding a RID-like DNA methyltransferase and constructed knocked-out ΔPaRid defective mutants. Crosses involving P. anserina ΔPaRid mutants are sterile. Our results show that, although gametes are readily formed and fertilization occurs in a ΔPaRid background, sexual development is blocked just before the individualization of the dikaryotic cells leading to meiocytes. Complementation of ΔPaRid mutants with ectopic alleles of PaRid, including GFP-tagged, point-mutated and chimeric alleles, demonstrated that the catalytic motif of the putative PaRid methyltransferase is essential to ensure proper sexual development and that the expression of PaRid is spatially and temporally restricted. A transcriptomic analysis performed on mutant crosses revealed an overlap of the PaRid-controlled genetic network with the well-known mating-types gene developmental pathway common to an important group of fungi, the Pezizomycotina.